Recent progress in the design and fabrication of multifunctional structures based on metamaterials - Yuan, Xujin; Chen, Mingji; Yao, Yin; Guo, Xiaogang; Huang, Yixing; Peng, Zhilong; Xu, Baosheng; Lv, Bowen; Tao, Ran; Duan, Shenyu; Liao, Haitao; Yao, Kai; et al. (Current opinion in solid state & materials science, 2021)
•Metamaterials became hotspot in electromagnetics, acoustics, and mechanics fields.•Since the integration of mechanical features and specific functions is still a challenge, the application of metamaterials has so far been limited.•Researches emerge in incorporating multifunctional design into a single structure.•Advances in design of multifunctional structures based on metamaterials are reviewed. Metamaterials, with unconventional properties realized through various ingenious designs of micro-architectures, have become a recent research hotspot in the fields of electromagnetics, acoustics, mechanics, and physics. Since the integration of mechanical features and specific functions is still a challenge, the application of metamaterials has so far been limited. The research in relevant areas has shown a clear trend of incorporating the multifunctional design into a single integrated structure. Here, we review the latest advances in the design and fabrication of multifunctional structures based on metamaterials, covering three main aspects, i.e., the direct design of mechanical metamaterials and their multifunctional structures, the intelligent multifunctional structures with shape-shifting capabilities, the metamaterials-based design to achieve both the load bearing capability and other specific functions. We emphasize the important roles that the mechanics-driven designs play, as well as the mechanisms and other key aspects behind the multifunctional structures. The structure-level innovations could not only improve multifunctional features, but also pave the way to function fusion structures that allow the incorporation of ‘conflicting’ functions into a single structure.